The new Arab public sphere - Āyish, Muḥammad ʻIṣām (Medien und politische Kommunikation-- Naher Osten und islamische Welt, 2008)
The introduction of satellite television and Web-based communications in traditional societies are often taken as manifestations of a new more democratic public sphere. In the book this Western intellectual tradition is taken to task for failing to grasp the real dynamics of an Arab public sphere that has yet to be realized. The author argues that we could not conceive of the Arab public sphere outside the boundaries of sustainable egalitarian and participatory political developments in Arabian societies. Ayish harnesses the notion of 'Islamocracy' or Islamic democracy to put forward a new pub